Tracks of a Rolling Stone - Coke, Henry J. (Henry John), 1827-1916 (Salt Lake City, UT : Project Gutenberg, 1996)
"Tracks of a Rolling Stone" by Henry J. Coke is a memoir written in the early 20th century. The narrative offers a reflective account of the author's early life, characterized by vivid reminiscences of childhood experiences and connections to historical events and notable figures of his time. Through engaging storytelling, Coke explores themes of memory, childhood innocence, and the transition into adulthood while sharing anecdotes from his own life, including encounters with royalty and military figures. The opening of the memoir sets a contemplative tone as Coke muses about the fleeting nature of childhood memories and their validity. He begins by questioning the nature of our recollections and pondering the significance of early experiences. As he recounts his first memories surrounding the death of King George IV, along with humorous anecdotes from his childhood interactions at his father's estate, the vibrant details draw readers into his youth. The initial chapters present a tapestry of significant life moments, blending humor with poignant reflection, as the author transitions from innocent observations of the world to the realities of life, including education and family affiliations. The blend of light-hearted storytelling and introspective insights suggests that readers will find both entertainment and contemplation in the pages ahead. (This is an automatically generated summary.)
Release date is 1996-04-01
Transcribed from the 1905 Smith, Elder, & Co. edition by David Price. Second proofed by Margaret Price
Keywords: Coke, Henry J. (Henry John), 1827-1916; West (U.S.) -- Description and travel